Pharmacokinetics and pharmacodynamics of oral oxycodone in healthy human subjects: role of circulating active metabolites - Lalovic, Bojan; Kharasch, Evan; Hoffer, Christine; Risler, Linda; Liu-Chen, Lee-Yuan; Shen, Danny D (Clinical pharmacology and therapeutics, 2006)
In vitro experiments suggest that circulating metabolites of oxycodone are opioid receptor agonists. Clinical and animal studies to date have failed to demonstrate a significant contribution of the O-demethylated metabolite oxymorphone toward the clinical effects of the parent drug, but the role of other putative circulating active metabolites in oxycodone pharmacodynamics remains to be examined. Pharmacokinetics and pharmacodynamics of oxycodone were investigated in healthy human volunteers; measurements included the time course of plasma concentrations and urinary excretion of metabolites derived from N-demethylation, O-demethylation, and 6-keto-reduction, along with the time course of miosis and subjective opioid side effects. The contribution of circulating metabolites to oxycodone pharmacodynamics was analyzed by pharmacokinetic-pharmacodynamic modeling. The human study was complemented by in vitro measurements of opioid receptor binding and activation studies, as well as in vivo studies of the brain distribution of oxycodone and its metabolites in rats. Urinary metabolites derived from cytochrome P450 (CYP) 3A-mediated N-demethylation of oxycodone (noroxycodone, noroxymorphone, and alpha- and beta-noroxycodol) accounted for 45% +/- 21% of the dose, whereas CYP2D6-mediated O-demethylation (oxymorphone and alpha- and beta-oxymorphol) and 6-keto-reduction (alpha- and beta-oxycodol) accounted for 11% +/- 6% and 8% +/- 6% of the dose, respectively. Noroxycodone and noroxymorphone were the major metabolites in circulation with elimination half-lives longer than that of oxycodone, but their uptake into the rat brain was significantly lower compared with that of the parent drug. Pharmacokinetic-pharmacodynamic modeling indicated that the time course of pupil constriction is fully explained by the plasma concentration of the parent drug, oxycodone, alone. The metabolites do not contribute to the central effects, either because of their low potency or low abundance in circulation or as a result of their poor uptake into the brain. CYP3A-mediated N-demethylation is the principal metabolic pathway of oxycodone in humans. The central opioid effects of oxycodone are governed by the parent drug, with a negligible contribution from its circulating oxidative and reductive metabolites.